2017
DOI: 10.1136/archdischild-2016-312307
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life among children with spina bifida in Uganda

Abstract: Urinary continence and family size are potentially modifiable, the former by simple and inexpensive medical management. Enhanced investment in community-based rehabilitation and support is urgently needed. Delivery of family planning services is a national priority in Uganda, and should be discussed with families as part of holistic care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…Neural tube defects (NTDs) are a group of severe congenital disorders associated with substantial mortality, morbidity, long‐term disability, and psychological and economic costs . Many NTDs are preventable with folic acid, and long‐term survival and quality of life among those living with NTDs can be improved through access to appropriate clinical care and rehabilitative services . However, efforts for primary prevention and addressing the needs of those living with NTD have been hampered by a lack of transparent prevalence estimates to quantify the burden, especially in resource‐poor settings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neural tube defects (NTDs) are a group of severe congenital disorders associated with substantial mortality, morbidity, long‐term disability, and psychological and economic costs . Many NTDs are preventable with folic acid, and long‐term survival and quality of life among those living with NTDs can be improved through access to appropriate clinical care and rehabilitative services . However, efforts for primary prevention and addressing the needs of those living with NTD have been hampered by a lack of transparent prevalence estimates to quantify the burden, especially in resource‐poor settings.…”
Section: Introductionmentioning
confidence: 99%
“…1 Many NTDs are preventable with folic acid, [2][3][4] and long-term survival and quality of life among those living with NTDs can be improved through access to appropriate clinical care and rehabilitative services. [5][6][7] However, efforts for primary prevention and addressing the needs of those living with NTD have been hampered by a lack of transparent prevalence estimates to quantify the burden, especially in resource-poor settings. The Modell Database of Congenital Disorders (MGDb) was developed recently to estimate the birth prevalence of congenital disorders globally.…”
Section: Introductionmentioning
confidence: 99%
“…We recently found that male sex, large family size, urinary incontinence and hydrocephalus were all associated with poorer self-reported quality of life (QOL) among 62 children aged 10–14 with spina bifida from Eastern Uganda 1. A limitation of this study was the absence of corresponding QOL scores for unaffected Ugandan children.…”
mentioning
confidence: 90%
“…Two studies reported various levels of correlation between PBMs and other outcome measures in SB [21,54]. Child self-reported HUI3 utility scores were not found to be highly correlated with VAS scores (r = 0.488) [54].…”
Section: Convergent Validity: Comparing Measuresmentioning
confidence: 99%
“…The sample sizes of relevant study groups ranged from 13 [15] to 770 [44]. Fourteen studies included data relating to CP [22, 33, 35, 36, 39, 46, 48-51, 53, 55, 57, 58], six included data relating to SB [21,38,51,52,54,56] and five included data relating to childhood hydrocephalus [40][41][42][43]45]. Data for a range of other relevant conditions were also found in either single studies or from extractable subgroups, these included muscular dystrophy [34,44], spinal muscular atrophy [47], Morquio A syndrome [37], congenital clubfoot [59] and microcephaly [51].…”
Section: Study and Patient Characteristicsmentioning
confidence: 99%